Local Scour Mechanism of Offshore Wind Power Pile Foundation Based on CFD-DEM - Qin Liu; Zhe Wang; Ning Zhang; Hongyu Zhao; Lei Liu; Kunpeng Huang; Xuguang Chen (Journal of Marine Science and Engineering, 2022)
The local scour around offshore pile foundations often seriously affects the normal operation of offshore wind power. The most widely used numerical simulation method in the study of local scour is the Euler two-fluid model (TFM). However, the contact effect between sediment particles is neglected in this model. Thus, the momentum and energy transfer between sediment particles and the fluid is not realistically reflected, which limits its significance in revealing the mesoscopic mechanism of local scour. Therefore, the computational fluid dynamics-discrete element method (CFD-DEM) numerical model was applied in this study, which fully considers the contact between solid particles and momentum transfer between two phases. The model was first verified by experimental data of a local scour test under clear water scour. Then, the mechanism of local scour was further discussed from macro and micro perspectives. The results showed that CFD-DEM could be effectively used to study the local scour around a pile foundation. The local scour was comprehensively affected by flow velocity, gravity, fluid force, drag force, and interaction between particles, etc. Although the maximum average drag force happened in the area about 90° from the direction of incoming flow, the maximum scour depth always occurred at about 45°. Corresponding findings and conclusions can be used for future reference when designing and protecting the offshore wind power pile.